Enhancement of Anti-Staling Properties of Rice Bread Through Fermentation Rice Flour with Three Lactic Acid Bacteria - Zhiqi Wang; Zhaosen Yuan; Xinlai Dou; Wanshan Yang; Huining Zhang; Yue Zhang; Fenglian Chen; Yanling Hao (Foods)
This study investigated the effects of Lactococcus lactis subsp. 1.2472 (L)-, Streptococcus thermophilus 1.2718 (S)-, and thermostable Lactobacillus rhamnosus HCUL 1.1901-1912 (T)-fermented rice flour with inoculum levels of 3–11% (w/w) on rice bread staling. Optimal staling resistance was achieved, as follows: 9% L-fermented rice bread (LRB), 7% T-fermented rice bread (TRB), and 5% S-fermented rice bread (SRB). Lactic acid bacteria-fermented rice flour significantly enhanced hydration properties. LF-NMR analysis revealed that T21 (strongly bound water) and T22 (weakly bound water) relaxation times decreased, while T23 (free water) increased with prolonged storage. Fermented-rice-flour groups had significantly more strongly bound water than the control group on 7 d. The optimized formulations exhibited exceptional volumetric stability with specific volume change rates of 17.63% (LRB), 17.60% (TRB), and 19.58% (SRB), coupled with maximal porosities of 10.34%, 9.05%, and 9.41%, respectively. This study provides a theoretical foundation for improving rice bread’s anti-staling properties.